1988
DOI: 10.1007/bf01790766
|View full text |Cite
|
Sign up to set email alerts
|

Outcome prediction in extradural haematomas

Abstract: Extradural haematoma (EDH) is generally a condition of young adult males. It represents only a small percentage of the total number of head injuries admitted to a neurosurgical service, but it must be differentiated from simple concussion, and this means that it is considered in a large number of patients. EDH has the potential for a low mortality rate because of its extraaxial location, but in practice it is approximately 10%. Our results show that about 40% of EDH present with vomiting or nausea and no focal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 11 publications
3
23
0
3
Order By: Relevance
“…Miller et al 9 reported that 183 patients with intracranial hemorrhage after "minor" head injury arrived in an alert condition with a GCS score of 15; 57% had no clinical signs. Likewise, Cook et al 10 reported that among 100 patients with traumatic epidural hematoma and GCS of 14 or 15, 40% had nausea or vomiting but no focal neurological signs. Although it is desirable to have cranial CT scans for all patients with TBI, it can be recognized that this is not viable everywhere.…”
Section: Discussionmentioning
confidence: 97%
“…Miller et al 9 reported that 183 patients with intracranial hemorrhage after "minor" head injury arrived in an alert condition with a GCS score of 15; 57% had no clinical signs. Likewise, Cook et al 10 reported that among 100 patients with traumatic epidural hematoma and GCS of 14 or 15, 40% had nausea or vomiting but no focal neurological signs. Although it is desirable to have cranial CT scans for all patients with TBI, it can be recognized that this is not viable everywhere.…”
Section: Discussionmentioning
confidence: 97%
“…Mortality following treatment of EDH varies from 5 to 43 percent (Cook et al, 1988;Jamjoom et al, 1992;Phonprsert, 1980;. Mortality is low (5 to10 percent) in children and increases sharply in those over age 40 (35 to 50 percent).…”
Section: Outcomementioning
confidence: 99%
“…In some studies the size of the hematoma, rather than its location, the degree of midline shift were the most influential in deciding in favor of surgical treatment in asymptomatic significant EDH [22,23]. But temporal location of EDH with heterogeneous density in patients whose CT scan was performed <6 hours after trauma had a higher risk of hematoma growth and thus should be treated surgically [24].…”
Section: Vmentioning
confidence: 99%